Investigating the problems experienced by virtual team members engaged in requirements elicitation - De Abrew, Upuli Kanchana (Rhodes University, Faculty of Commerce, Department of Information Systems, 2013)
The constant acceleration in the rate of technological innovation, and the ever growing emphasis on the importance of information for competition has seen organisations around the world strive for the technologies that give them global customer reach. One of the most pervasive technological innovations developed is the internet, and its unique quality of being able to draw people from across the world together in one virtual space has given birth to the concept of virtual teams. Organisations have seized the advantages of such virtual teams to give them the cost and time reductions they need to stay competitive in the global marketplace. In the software industry, where product and service development is always a race against time, forward thinking software companies in the developed world have taken full advantage of the cost and time saving benefits that virtual teams have to offer. In addition, the rate of expansion of technology and software to support such teams is also growing exponentially, offering increasingly faster ways of virtual working. Despite the immense advantages offered by such teams, South African software development companies do not seem to engage in distributed work to any great degree. The importance of this research rests on the belief that South African software development companies will be unable to avoid engaging in distributed software development if they are to achieve and maintain competitiveness in the global marketplace. This research focuses on a sub-section of the software development process with a specific reference to South African software development. The requirements elicitation phase of software development is one of the initial stages of any software project. It is here that developers work with the users in order to identify requirements for the system to be built. It is acknowledged that other phases of distributed development also bring to bear their own problems, however, in the interests of scoping this research, only the requirements elicitation process is focused on. The research shows that most techniques of requirements elicitation can be adapted for use within the virtual environment, although each technique has its share of advantages and disadvantages. In addition, virtual team members experience problems during their general, day-to-day interactions, many of these arising from the dependence on technology for communication and task performance. The research identifies the problems in both categories, and develops a holistic model of virtual requirements elicitation to prevent or solve the problems experienced by virtual teams engaged in distributed requirements elicitation. The model is made up of three key frameworks, each of which prescribes actions to be taken to ensure the success of the virtual team within the requirements elicitation process. The model is verified through the testing of its critical success factors. Certain aspects of the model were adapted based on the findings of the study, but it was confirmed that the rationale behind the model is sound, indicating that it has the potential to solve the problems of virtual RE when implemented.
Keywords: Virtual work teams; Virtual work teams -- South Africa; System design System analysis